PERAN UMKM DALAM MENDUKUNG PERTUMBUHAN LOKAL DI WILAYAH KOTA MEDAN - Sari, Tria Manda; Ismail Lubis, Rahmad; Hanafi Nasution, Mifta; Darmawan, Aldy Fauzan; Wulandari, Sari (Politeknik Bisnis Indonesia, 2024)
In the Medan City region as well as elsewhere, micro, small, and medium-sized enterprises (MS Mes) play a critical role in foresting local economic growth. In addition to creating jobs, MSMEs, a sector that employs a lot of people, boost regional economic competitivenes by foresting innovation, producing locally, and offering goods and services that cater to local needs. With and emphasis on their effects on raising peoples incomes, lowering unemployment rates, and foresting the growth of associated industries like commerce and the creative sector, this study attempts to examine how MSMEs contribute to Medan Citys economic development. In addition, this study examines the difficulties Medan Citys MSMEs encounter in obtainingfunding, marketing, and technology. Using a qualitative approach, the researchs methodology involves gathering data trought a literature review and document analysispertaining to MSMEs and the local economy. It is intended that the findings of a study will help the government and other interestedparties create policies that promote the growth and sustainability of MSMEs in the area.